Types and Density of Aquatic Plants in the Parit Belanda Swamp, Rumbai Pesisir - Devi Lia Ariyanti; Windarti '; Efawani ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
Parit Belanda swamp is flood plane area located around the Parit BelandaRiver, Pekanbaru. This swamp is inhabited by various types of aquatic plants andthey almost cover the surface of the swamp. A study aims to understand the typesand density of the aquatic plant was conducted from November to December2015. Field sampling was done 2 times a month. The plants were then identifiedbased on Van Steenis (1981). Results shown that there were 6 species of aquaticplants present and they are belonged to 3 classes and 6 families. They arePaspalum commersoni, Eichhornia crassipes, Colocasia esculentum, Salvinianatans, Ipomoea aquatica and Pandanus tectorium. The most common plant isPaspalum commersoni (40.4-53.3 organisms/m2 , relative density 47.08-47.08 %)while the rarest was Colocasia esculentum (3.2-5.9 organisms/m2, relative density3.36-5.83 %). In general, the relative density of aquatic plants in the Parit BelandaSwamp can be categorized as rare to dense.Key words : Aquatic plants, Density,Parit Belanda swamp